Effect of chalcogen bonding on the packing and coordination geometry in hybrid organic–inorganic Cu(ii) networks. Issue 15 (24th March 2022) - Parisi, Emmanuele; Carella, Antonio; Borbone, Fabio; Chiarella, Fabio; Gentile, Francesco Silvio; Centore, Roberto
Abstract : The effect of chalcogen bonding interaction led to the interesting crystal packing and coordination geometry of copper(ii ) in novel organic–inorganic hybrids. Abstract : The effect of chalcogen bonding interaction led to the interesting crystal packing and coordination geometry of copper(ii ) in novel organic–inorganic hybrids. The reactions of organic bridging ligands 1, 2, 5-benzothiadiazole ( btd ) and 1, 2, 5-benzoselenazadiazole ( bsed ) with CuCl2 and CuBr2 by slow diffusion of two miscible solvents afforded three isomorphic 2D-network polymers, [CuCl2 ( btd )] n (1 ), [CuBr2 ( btd )] n (2 ), and [CuCl2 ( bsed )] n (3 ), and one molecular hybrid, CuBr2 ( bsed )2 (4 ). The crystal structures of these novel hybrids were determined by single X-ray crystallography. The three isomorphic hybrids consist of 2-D sheets in which [Cu(μ-X)2 ] n infinite linear chains running along the a axis are linked through N-coordinated molecules of btd and bsed along the b axis. On the other hand, the crystal packing of 4 is strongly influenced by the presence of the [Se⋯N]2 supramolecular synthon and Se⋯Br short interactions, all based on chalcogen bonding, that link the dimeric complex molecules into two-dimensional arrays parallel to the ac plane.